Effects of Monetary and Macroprudential Policies on Financial Conditions : Evidence from the United States - Zdzienicka, Aleksandra (IMF Working Papers; Working Paper ;, 2015)
The Global Financial Crisis has reopened discussions on the role of the monetary policy in preserving financial stability. Determining whether monetary policy affects financial variables domestically-especially compared to the effects of macroprudential policies- and across borders, is crucial in this context. This paper looks into these issues using U.S. exogenous monetary policy shocks and macroprudential policy measures. Estimates indicate that monetary policy shocks have significant and persistent effects on financial conditions and can attenuate long-term financial instability. In contrast, the impact of macroprudential policy measures is generally more immediate but shorter-lasting. Also, while an exogenous increase in U.S. monetary policy rates tends to reduce credit and house prices in other countries-with the effects varying with country-specific characteristics-an increase driven by improved U.S. economic conditions tends to have the opposite effect. Finally, we do not find evidence of cross-border spillover effects associated with U.S. macroprudential policies.